2012
DOI: 10.1210/jc.2012-1987
|View full text |Cite
|
Sign up to set email alerts
|

Adult Height in Short Children Born SGA Treated with Growth Hormone and Gonadotropin Releasing Hormone Analog: Results of a Randomized, Dose-Response GH Trial

Abstract: When started in adolescence, GH treatment significantly improves AH in short SGA children, particularly with GH 2 mg/m(2) · d during puberty. When SGA children are short at the start of puberty, they can benefit from combined GH/GnRHa treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 84 publications
1
35
1
3
Order By: Relevance
“…In contrast, Hokken-Koelega and colleagues [58] have shown that treatment with a higher dose of GH (2 mg/m 2 /day) during puberty resulted in a significantly better adult height than low-dose (1 mg/m 2 /day) GH treatment. Although GnRH analog treatment might reduce growth velocity, evidence suggests that combined GH and GnRH analog treatment may improve adult height in SGA children who are short at the start of puberty (<140 cm) and have a poor adult height expectation.…”
Section: Growth Hormone Treatment and Pubertal Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, Hokken-Koelega and colleagues [58] have shown that treatment with a higher dose of GH (2 mg/m 2 /day) during puberty resulted in a significantly better adult height than low-dose (1 mg/m 2 /day) GH treatment. Although GnRH analog treatment might reduce growth velocity, evidence suggests that combined GH and GnRH analog treatment may improve adult height in SGA children who are short at the start of puberty (<140 cm) and have a poor adult height expectation.…”
Section: Growth Hormone Treatment and Pubertal Developmentmentioning
confidence: 97%
“…Although GnRH analog treatment might reduce growth velocity, evidence suggests that combined GH and GnRH analog treatment may improve adult height in SGA children who are short at the start of puberty (<140 cm) and have a poor adult height expectation. These children might also need a higher GH dose [58]. …”
Section: Growth Hormone Treatment and Pubertal Developmentmentioning
confidence: 99%
“…However, in 17 patients with SRS in this study, puberty was postponed for 2 years with gonadotropin-releasing hormone analogue (GnRHa) due to a low predicted adult height. The effect of GnRHa on final height has been analysed in a cohort of patients with SGA, including patients with SRS 120,121 . This analysis suggested that the combination of GnRHa, started at the initiation of puberty and continued for at least 2 years, along with GH treatment, improves adult height in patients born SGA with a poor adult height prognosis.…”
Section: Bone Age Advancement and Pubertymentioning
confidence: 99%
“…Since treatment around the onset of puberty has been shown to produce limited effects52), Lem et al57) studied the effect of GH and gonadotropin releasing hormone analogue in a randomized trial. They concluded that when SGA children are short at the start of puberty, they could benefit from combined GH/GnRH treatment.…”
Section: Small For Gestational Agementioning
confidence: 99%